Effects of exogenous retinoic acid on ocular parameters in Guinea pigs with form deprivation myopia - Wu, Yajun; Feng, Yuliang; Yang, Jiasong; Fan, Hua; Yu, Zitong; Xie, Xiaolin; Dai, Yumeng; Huang, Xin; Li, Wensheng (Frontiers in Cell and Developmental Biology, 2023)
Aim: Myopia is a common chronic eye disease, this study is to investigate the effects of exogenous retinoic acid (RA) on intraocular parameters, especially choroidal thickness(CT) and retinal thickness(RT), in guinea pigs with form deprivation myopia(FDM). Methods: A total of 80 male guinea pigs were divided randomly into 4 groups:Control, FDM, FDM+RA, and FDM+Citral groups. The FDM + RA group were given 24 mg/kg RA dissolved in 0.4ml peanut oil; the FDM+Citral group was given citral 445 mg/kg dissolved in 0.4ml peanut oil; The other two groups were given 0.4ml peanut oil. After 4 weeks, the refractive error (RE), axial length (AL), and intraocular pressure (IOP) of all guinea pigs were measured, and the parameters of RT and CT were obtained using enhanced depth imaging optical coherence tomography(EDI-OCT). Results: After 4 weeks, both the RE and AL in the FDM and FDM + RA groups were increased, and the RT and CT in both groups were smaller than those in the Control group(p<0.05). Only the IOP of the right eye in the FDM + RA group increased significantly (p<0.05). The RT of the right eye of the 4 groups was compared:Control group > FDM+Citral group >FDM group> FDM+RA group. Compared with the RT of the left eye and the right eye among the 4 groups, the RT of the right eye in the FDM and FDM + RA groups was significantly less than that in the left eye(p<0.05). Moreover, the CT of the right eye in the Control group was greater than that in the other three groups (p<0.0001). There was no significant difference in the CT among the FDM, FDM + RA, and FDM+Citral groups (p>0.05). In contrast to the RT results, the CT results of the left and right eyes in the FDM+Citral group showed statistically significant differences(p<0.05). Conclusions: RA participates in the progression of FDM as a regulatory factor. Exogenous RA can increase the RE, AL, and IOP of FDM guinea pigs, and might aggravate the retinal thinning of FDM guinea pigs. Citral can inhibit these changes, but RA might not affect the thickness of the choroid.